2011
DOI: 10.1186/1743-422x-8-396
|View full text |Cite
|
Sign up to set email alerts
|

IPNV with high and low virulence: host immune responses and viral mutations during infection

Abstract: BackgroundInfectious pancreatic necrosis virus (IPNV) is an aquatic member of the Birnaviridae family that causes widespread disease in salmonids. IPNV is represented by multiple strains with markedly different virulence. Comparison of isolates reveals hyper variable regions (HVR), which are presumably associated with pathogenicity. However little is known about the rates and modes of sequence divergence and molecular mechanisms that determine virulence. Also how the host response may influence IPNV virulence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 56 publications
7
58
2
Order By: Relevance
“…This fact would suggest a high IFN or antiviral response in the sea bass gonad and a very low response in the brain, which could explain the low resistance of this fish species, but this needs to be confirmed at functional level. These results are in agreement with other studies in fish showing the upregulation of most of these genes after virus infection in several tissues or their antiviral function after cell line overexpression (Biacchesi et al, 2009;Chen et al, 2015;Feng et al, 2011;Rise et al, 2008Rise et al, , 2010Skjesol et al, 2011;Su et al, 2010;Sun et al, 2011;Xiang et al, 2011;Yang et al, 2011), and support the fact that the sequences identified in our study mediate the IFN activation cascade. In the case of tbk1, which is also activated by the TLR response, it is only upregulated in sea bass specimens infected with VNNV.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This fact would suggest a high IFN or antiviral response in the sea bass gonad and a very low response in the brain, which could explain the low resistance of this fish species, but this needs to be confirmed at functional level. These results are in agreement with other studies in fish showing the upregulation of most of these genes after virus infection in several tissues or their antiviral function after cell line overexpression (Biacchesi et al, 2009;Chen et al, 2015;Feng et al, 2011;Rise et al, 2008Rise et al, , 2010Skjesol et al, 2011;Su et al, 2010;Sun et al, 2011;Xiang et al, 2011;Yang et al, 2011), and support the fact that the sequences identified in our study mediate the IFN activation cascade. In the case of tbk1, which is also activated by the TLR response, it is only upregulated in sea bass specimens infected with VNNV.…”
Section: Discussionsupporting
confidence: 83%
“…Similar upregulation has been documented in the brain of sea bass and Atlantic halibut exposed to VNNV (Dios et al, 2007;Rise et al, 2010), and this supports our data. Moreover, these sensors are also upregulated by several fish RNA viruses or polyI: C in several tissues of fish, such as spleen, head-kidney, liver or intestine, as well as in some fish cell lines, leading to an increase in the type I IFN-mediated antiviral response (Feng et al, 2011;Rise et al, 2008Rise et al, , 2010Skjesol et al, 2011;Su et al, 2010;Yang et al, 2011). Moreover, fish rig1 and mda5 transient overexpression leads to the induction of ifn expression and confers an antiviral state (Biacchesi et al, 2009;Sun et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The length of VP5 can vary dramatically in IPNV (i.e. 28 aa to 133 aa) but the functional significance of such changes remains unclear (Skjesol et al 2011). The effect of the premature stop codons detected within TABV in this study are also unknown but did not correlate with the disease events of 2011 to 2013.…”
Section: Discussionmentioning
confidence: 61%
“…The expression levels of the fish RLR mRNAs were increased in various tissues upon infection by several viruses, such as SVCV, grass carp Ctenopharyngodon idellus reovirus (GCRV) and IPNV [72][73][74][75][76][77][78][79].…”
Section: Retinoic Acid Inducible Gene (Rig)-i-like Receptors (Rlrs) Imentioning
confidence: 99%